2004
DOI: 10.1258/135581904322716067
|View full text |Cite
|
Sign up to set email alerts
|

An holistic economic evaluation of an Aboriginal community-controlled midwifery programme in Western Sydney

Abstract: Net per client costs to the health service were modest. Quantitative evidence of improved antenatal outcomes was limited, but qualitative evaluation suggested the service was strongly valued. The outcomes examined in this study were broader than those used in conventional forms of economic evaluation and this enabled identification and analysis of more diverse sources of value from this programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
134
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(135 citation statements)
references
References 0 publications
0
134
0
1
Order By: Relevance
“…Interventions in Guatemala [83][84][85] attempted to integrate local Indigenous practices with biomedical care practices but did not sufficiently involve Indigenous community members in the design or implementation stages, which led to a birthing centre that was unused for three months and services that excluded Mayan midwives 83,90,91 and the United States of America 81,91 provide examples of successful culturally safe maternal healthcare programs that have been community controlled. These programs empowered participants, built trusting patient-provider relationships, improved preconception health knowledge and improved the health outcomes of mothers and babies 83,90,91 . To increase the likelihood of success, culturally safe programs should be developed with the input and participation of the target Indigenous community 83,90,91 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions in Guatemala [83][84][85] attempted to integrate local Indigenous practices with biomedical care practices but did not sufficiently involve Indigenous community members in the design or implementation stages, which led to a birthing centre that was unused for three months and services that excluded Mayan midwives 83,90,91 and the United States of America 81,91 provide examples of successful culturally safe maternal healthcare programs that have been community controlled. These programs empowered participants, built trusting patient-provider relationships, improved preconception health knowledge and improved the health outcomes of mothers and babies 83,90,91 . To increase the likelihood of success, culturally safe programs should be developed with the input and participation of the target Indigenous community 83,90,91 .…”
mentioning
confidence: 99%
“…These programs empowered participants, built trusting patient-provider relationships, improved preconception health knowledge and improved the health outcomes of mothers and babies 83,90,91 . To increase the likelihood of success, culturally safe programs should be developed with the input and participation of the target Indigenous community 83,90,91 . The existence of health inequities between Indigenous and non-Indigenous women in urban areas reinforces the need to address structural barriers to health.…”
mentioning
confidence: 99%
“…All studies but two were conducted in high-income, OECD-member countries: Australia ( n  = 6) (Nel and Pashen 2003; Jan et al 2004; NSW Health 2005; Panaretto et al 2005, 2007; Kildea et al 2012), the United States of America (USA) ( n  = 4) (Julnes et al 1994; Thompson et al 1998; Jewell and Russell 2000; Marsiglia et al 2010), the United Kingdom (UK) ( n  = 2) (Mason 1990; Parsons and Day 1992) and Israel ( n  = 1) (Bilenko et al 2007). The two exceptions were conducted in Peru (McQuestion and Velasquez 2006; Gabrysch et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Of the eight cost-analysis studies, six found interventions would be cost-saving over time relative to the comparison [17],[20],[22],[24],[25],[30]. The study of the group midwifery program in the Top End of Australia found no significant cost differences between the provided intervention and usual care [33], while the urban midwifery program was deemed not cost-saving although qualitative results demonstrated that patients valued the service [11]. The cost-benefit analyses carried out all found the injury prevention interventions to be cost-beneficial in that they had benefit-cost ratios above one [34].…”
Section: Resultsmentioning
confidence: 99%